Increasing VO2 Max Through Circuit Training for Extracurricular Football Students at SMA Negeri 5 Soppeng - Akbar, Ilham; Hakim, Hikmad; Sahabuddin, Sahabuddin (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This research aims to determine the effect of circuit training on increasing VO2 Max in extracurricular football students at SMA Negeri 5 Soppeng. The population of this study were all students of SMA Negeri 5 Soppeng with a research sample of 20 students selected as a total population and a group division system using ordinal maching. The data analysis techniques used are descriptive, data normality tests, homogeneity tests and t-tests using the SPSS program. The research results show that; There is an influence of circuit training on increasing VO2 Max in extracurricular football students at SMA Negeri 5 Soppeng. Increase in VO2 Max in extracurricular football students at SMA Negeri 5 Soppeng with an increase from an average score of 30.2500 to 44.3100.